The Oldest Ceramics Kiln in the Russian Far East. Issue 1 (3rd April 2019) - Zhushchikhovskaya, Irina S.; Nikitin, Yuri G.
Abstract : This article analyzes the remains of a pottery kiln excavated at the Chernyatino 2 site in the Primor'e District on the southern mainland of the Russian Far East adjacent to the Korean Peninsula and northeastern China. The kiln's remains have been assigned to the Krounovskaia culture of the Paleometal period and preliminarily dated to the early 1st millennium CE. The kiln is characterized by: 1) a subrectangular floor plan excavated into the soil and slightly sloped; 2) fuel and firing sections located at different levels and separated by a low step; 3) small size; 4) a tunnel-like clay dome on a stick frame. Many damaged dome fragments were found near the subrectangular kiln excavation. Based on the results of pottery sample examination, in particular scanning electron microscope [SEM] analysis, the firing temperatures in the kiln were 750–900° С. The kiln is the earliest structure for firing pottery so far recorded in the southern Russian Far East. Such kilns were invented on the Korean Peninsula in the 3rd–4th centuries CE.